Pola Tidur Rasulullah SAW Sebagai Pencegahan Insomnia DiKalangan Santri: Studi Kasus Pesantren Darul Ibtihaj Medan Tembung - Muhammad Rizky; Agusman Damanik (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Sleep is a fundamental human need that plays a crucial role in maintaining both physical and mental health. Insomnia, or sleep disorders, is a common issue among students (santri) in Islamic boarding schools (pesantren), which can be caused by various factors such as a demanding study schedule, irregular sleep habits, and an unhealthy lifestyle. In some cases, lack of sleep can negatively impact daily activities and lead to poor living patterns. This study aims to analyze the sleeping patterns of Prophet Muhammad (SAW) as a method to prevent insomnia among students at Darul Ibtihaj Islamic Boarding School.